The principles and practice of modal counterpoint - Green, Douglass M. (Douglass Marshall), 1926-1999 (Routledge, 2011)
Covering modal music from Gregorian chant through the seventeenth-century, The Principles and Practice of Modal Counterpoint is a comprehensive textbook combining stylistic composition, theory and analysis, music history, and performance. By supplementing a modified species approach with a wealth of complete musical examples and historical information, this textbook thoroughly joins principle with practice, providing a truly immersive experience in the study of modal counterpoint and familiarizing students with modal repertoire.